Prevalence of Haemoprotozoan Infection in Gir Cattle in and around Junagadh, Gujarat - Swami, SB; Patel, JS; Kumar, Binod; Parmar, VL; Bilwal, AK; Patel, BR (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was carried out on a total of 250 Gir cattle, which covered those presented to the Veterinary Clinical Complex of the College  in Junagadh (Gujarat) for therapeutic measures and some from Gaushala near to Junagadh region. The animals were screened for  common hemoprotozoan infection based on blood smear examination to record the prevalence rate of infection. The overall prevalence  of hemoprotozoan infections recorded on the basis of microscopic examination of blood smears was 35.20 %. Out of these, 64 (25.60%)  were positive for Theileria spp., 20 (8%) for Babesia spp., and 4 (1.6%) for Anaplasma spp. the highest prevalence was recorded in April  (64.70%), followed by March (57.14%) and February (42.85%). The lowest prevalence was recorded in the month of December (5.88%).  The highest prevalence was recorded in the summer season (40.71%), followed by rainy (34.37%) and winter season (19.56%). The highest  prevalence of hemoprotozoan infection (41.86%) was recorded in Gir cattle of 3 to 8 years age group followed by 32.35% in 6 months  to 3 years age group, and the lowest prevalence was recorded (24.32%) in older animals 8 years and above age group.
Keywords: Age; Gir cattle; Haemoprotozoan infection; Prevalence; Season